Determination of Caffeine and Trace Minerals Contents in Soft and Energy Drinks Available in Basrah Markets - Mohammed, Sarmad G.; Al-Hashimi, Alaa G.; Al-Hussainy, Khadeeja S. (Pakistan Journal of Nutrition, 2012)
Ten brands of beverages (soft and energy drinks) consumed in Basrah governorate/Iraq, were analyzed for its pH, trace minerals and caffeine contents. The beverages included (O2, Boom Boom, Wild Tiger, Power horse, Kalaschnikow, Pit bull, Pepsi, Mountain dew, Riviere and Barbican). Results showed that the pH of the beverages ranged from 2.75-3.66. Iron and Calcium were found in all beverages, Cadmium was found in (Boom Boom, Pit bull, Kalaschnikow and Barbican). Lead was found only in O2, Power horse, Kalaschnikow and Riviere. Manganese was found in Boom Boom, Wild Tiger, Power horse, Pit bull and Riviere. Caffeine was found in all beverages except Riviere and Barbican, the highest level of caffeine was in Kalaschnikow (103.13 mg/100 ml) when compared with the other beverages.